Japanese Encephalitis Vaccination in Children Population of Nepal During the year 2005, 2006 and 2008 - Joshi, Durga Datt (Journal of Nepal Paediatric Society, 2009)
Japanese Encephalitis (JE) is caused by a Flavivirus that, in a proportion of human cases, causes severe encephalitis leading to death or sometimes permanent disablement. It is a zoonotic disease, transferred from animals (commonly pigs or wild birds) by a mosquito vector to humans. In Southeast Asia it is thought to cause up to 50000 clinical cases and 10000 deaths per year. JE vaccination programme was carried out in high risk districts of Nepal. Japanese encephalitis vaccination was carried out during the years 2005, 2006, 2008 and 2009. The data collected from primary and secondary sources from the District Health Offices and other concerned central offices of the Department of Health Services, was tabulated and analysed. Thirty-five lakh of JE vaccine doses was procured by the Ministry of Health during the year 2006/2007. This vaccine was used in children under 15 years of age of 12 districts of JE risk and high-risk areas of Nepal. It was found that during the year 2005; 85% children in Banke and 81% in Kailali were vaccinated against JE. In Kailali and Banke districts it was found to be about 103% coverage in children population targeted, in Dang district it was 100% coverage, and in Bardiya district it was 73% coverege but in Rupandehi and Kanchanpur districts it was only about 40% and 41% respectively. JE vaccine coverage was very low in two Rupandehi and Kanchanpur districts during 2005 and 2006 and very high coverage during the year 2008. JE vaccination coverage results for the year 2009 have not been made available yet due to unavailability of data. This type of mass vaccination campaign needs regularlity, mass awareness and health education programme should be carried out before JE vaccination campaign in the children in the future. Key words: Japanese Encephalitis, flavivirus, zoonotic, vector borne, lyophilized vaccine. doi: 10.3126/jnps.v29i2.2045 J. Nepal Paediatr. Soc. Vol 29, No. 2, pp.85-91